The Ancient World-View and Cosmologic Perception of the Arctic Peoples in the Physical Picture of the World - Satanar, Marianna Timofeyevna (Journal of History Culture and Art Research, 2018)
The article focuses on the interdisciplinary study of the cosmologic views among the Arctic peoples on the material of oral works – olonkho, nimkan, nimngakan, olongko. An attempt is made at integrating the humanities and sciences with the priority on the convergence. Following the necessity to form a new world-view guideline, the synthesis of the empirical methods and meta-scientific knowledge are considered the starting point in developing the new values of the systemic thinking. The suggested approach shows practical steps towards expansion and deepening of the basics of scientific rationality in humanities (for the highest result of scientific knowledge is considered to be the perception of the universal and objective natural laws in subjects and phenomena in their life process) on the one hand, and humanization and humanitarization of sciences, which provide an important moral category on the other hand. The authors of the study use the methods widely used in folklore study, as well as the less-frequently used modern approaches – synergetics, hermeneutics, and the systemic method. Ancient samples of the Arctic peoples’ epic heritage is brought forward to the inter-disciplinary crossing point, where integration of methodologies allows to remove the dividing line between the rational, irrational, and transcendental categories of human mind, which are directly connected to the problem of studying the very phenomenon of storytelling – a complicated and multi-lateral object of study. Human integrity, formulated by M.S. Kagan as that of “the measure of all things”, serves as the uniting basic fundament of analyzing science and culture. Under the given work such basis serves as an approach to the epic work as the product of storyteller’s work. Comparative analysis revealed a certain semantic and structural unity between the cosmologic perception in the Arctic peoples’ ancient world-view and the modern physical picture of the world. This leads to understanding the strong cognitive unity of the world-formation, which is directly linked to the concept of humanism. The work approbates the methodology of comparison and extrapolation of the different knowledge forms during which a kind of “writing-in” of the old mythological world-views into the fundamental natural laws occurs.